Association of a cleaner-burning stove with blood pressure in adults in rural Malawi. - Michael N Bates; Graham Flitz; Sarah Rylance; Andrew Naunje; Frank Mbalume; Deborah Havens; Maia Lesosky; Steven B Gordon; Kevin Mortimer; John R Balmes (PLoS ONE)
Background Hypertension is a leading risk factor for cardiovascular disease, and its association with household air pollution (HAP) in sub-Saharan Africa is understudied. Main objective To investigate the association between blood pressure (BP) and HAP exposure in a population-based cohort in rural Malawi. Materials and methods In the Chikwawa district, the site of a previous randomized controlled trial of a cleaner-burning cookstove intervention (the Cooking and Pneumonia Study or CAPS), we recruited 1,481 randomly selected adults. A subset (∼21%) were from participating households in CAPS. This cross-sectional analysis investigates associations of BP with stove type and, in a sample of participants, with particulate matter ≤ 2.5 μm diameter (PM2.5) and carbon monoxide (CO), both measured using 48-hour personal monitoring. Two main types of analysis were conducted: a) assessment of differences in mean systolic BP (SPB) and diastolic BP (DBP) among three groups based on stove use/type and b) assessment of the associations between PM2.5 and CO with mean SBP and DBP; both analyses using multivariable linear regression. Results Of the 1481 participants, 910 provided BP data. There was no difference for either mean SBP or DBP between the CAPS intervention and control groups. However, when comparing all CAPS participants (i.e., those provided cleaner-burning cookstoves by study's end) to the non-CAPS group, mean SBP was reduced (-3.53 mmHg, 95% CI:-6.54,-0.52), but not DBP (-0.73 mmHg, 95% CI:-2.36,0.90). Of these, 599 participants also had ≥24 hours personal exposure monitoring data. Neither the log mean PM2.5 concentration nor the log mean CO concentration was associated with either SBP or DBP. Discussion In this cross-sectional study in non-pregnant adults to measure both exposure to HAP and blood pressure in sub-Saharan Africa, we found evidence for an association between receiving a cleaner-burning cookstove and reduced SBP, but no evidence for an association between BP and personal exposure to PM2.5 or CO.